(untitled) (Papeles, 2022)
Introduction: Studies involving the prescription of educational assessment in Latin American teacher training courses have been a recent practice among researchers. However, there is little research dedicated to the analysis of the theoretical discussions that are prescribed in these courses. The objective of this article was to analyze the bibliographies prescribed to teach educators best assessment practices in specific course curriculum related to this area in Latin American training courses for Physical Education teachers, identifying the authors, their nationalities, countries in which the authors are prescribed, and their academic production background about assessment practices. Methodology: This project is a qualitative and exploratory investigation, based on documentary analysis of the type of the type of author’ networks that use Gephy software as a support tool. The studied sources were 83 references prescribed in 14 discipline plans of 13 Latin American institutions. Results and discussion: The results show a predominance of Spanish authors, the presence of authors from the same country of origin of the institution where the discipline is taught, the circularity of Latin American authors outside the country of origin, and authors who have generated a background for the study of assessment practices. Conclusions: In each context, the courses prescribe bibliographies/authors that allow students in the process of teacher training to bring the study of evaluation closer to the context of future professional performance.